Books from an environmental perspective-Part 1 environmental impacts of paper books sold in traditional and internet bookshops. - Borggren, Clara (The International Journal of Life Cycle Assessment)
Purpose The sale and distribution of books are activities that have changed through increased use of the internet. The main aim of this paper was to determine the potential environmental impacts of paper books and identify key issues determining the magnitude of those impacts. A second aim was to study the environmental difference between a paper book bought in a traditional bookshop and through an internet bookshop. In addition, areas with a lack of data and major uncertainties were to be noted. Materials and methods A screening life cycle assessment was performed on an average hardback novel produced and read in Sweden. The data used were general data from Ecoinvent 2.0 and site specific data from companies participating in the study, whenever average data were not available. Results and discussion The results showed the most important processes to be pulp and paper production. However, if a substantial distance was travelled by car, to buy a book or collect it, this had a major influence on the environmental performance. Comparing the two bookshop alternatives, the results showed a slight benefit for the internet bookshop due to fewer books being returned to the publisher and the avoidance of energy use at the traditional bookshop. The buyer of a book could significantly influence the total impact by choosing to walk to the bookshop or to combine the trip with several other activities to decrease the impact of the travel per activity performed. When books ordered via the internet were sent by postal services directly to the end consumer, the climate change impact was lowered. Conclusions This study showed that, in addition to the paper used, the way books are bought and distributed, including possible personal transportation, can significantly affect the total environmental impact of paper books. The impact per book read can be significantly decerased by sharing books with others.